Small-Signal stability analysis of MMC-HVDC system with saturated transformer - Hanwen Wang; Yang Wang; Xianyong Xiao; Yunzhu Chen; Shupeng Li; Zhijun Er; Zhenbin Li (International Journal of Electrical Power & Energy Systems, 2025)
Transformer saturation has a significant impact on the stability of HVDC systems. While traditional research has primarily focused on LCC-HVDC systems, studies on MMC systems remain limited. Given the anticipated dominance of MMC technology in the future, it is crucial to understand the instability risks MMC-HVDC systems face under transformer saturation. The key challenge lies in accurately modeling the harmonic coupling induced by the saturated transformer and analyzing its interaction with MMC-HVDC systems. To tackle this challenge, the harmonic state space (HSS) technique is employed in this paper to model the harmonic coupling in MMC-HVDC systems with saturated transformers. Initially, a saturable transformer model is developed, with the excitation curve fitted using a polynomial approach. This model is then interconnected with the MMC-HVDC system to establish a comprehensive HSS model for analysis. To facilitate the stability analysis, the HSS model is further transformed into a single-input–single-output impedance representation, enabling the effects of harmonic coupling to be observed through impedance curves. Finally, a Nyquist-based stability analysis is performed to explain why MMC-HVDC systems are more prone to instability under transformer saturation and to identify key factors contributing to this instability. Simulation and experimental results validate the theoretical analysis.